Social change in Ireland (1922-2000) : as reflected in recent cinema - Wakefield, Joana Margarida dos Santos Gomes (2011)
Esta tese propõe-se a investigar a forma como as mudanças socio-históricas que afectaram a República da Irlanda entre 1922 e 2000 são representadas no cinema recente. Particular ênfase irá ser dada aos dois temas mais comuns: a Igreja Católica e a familia nuclear. Será também dada atenção ao facto de haver uma grande tendência no cinema recente para retratar o passado da República da Irlanda de modo a permitir que os espectadores reflitam sobre a presente situação do país. ABSTRACT: This thesis proposes an investigation of how the socio-historic changes which occured in Ireland between 1922 and 2000 are represented in recent cinema. Particular emphasis will be placed on its most common themes: the Catholic Church and the Irish nuclear family unit. Attention will also be given to the fact that recent cinema has a strong tendency to portray Ireland’s past in a way that allows spectators to reflect on the country’s current situation.